Cultivation effects of Saudi newspapers on estimates of expatriate crime - Sabri, Ahmed (AUC Knowledge Fountain, 2016)
For years, scholarly work examined the media effects on audience and how they view and understand the world. In particular, media can play a role in shaping how an individual views crime and criminals. Using cultivation theory, this study examines the effects of Saudi Arabian print media (newspapers) on nationals and expatriates living in Jeddah, Saudi Arabia. Surveys from 526 respondents were analyzed and hypotheses tested finding; there was no relationship between level of readership and personal perceptions of expat crime levels; there is no statistical significance between the level of readership and further judgments on how to deal with expat crimes and no resonance effect was found. On the other hand, group membership has a significant effect on estimations of expat crime levels.